A transient helix in the disordered region of dynein light intermediate chain links the motor to structurally diverse adaptors for cargo transport - Celestino, Ricardo; Henen, Morkos A.; Gama, José B.; Carvalho, Cátia; McCabe, Maxwell; Barbosa, Daniel J.; Born, Alexandra; Nichols, Parker J.; Carvalho, Ana X.; Gassmann, Reto; Vögeli, Beat (PLoS biology, 2019)
All animal cells use the motor cytoplasmic dynein 1 (dynein) to transport diverse cargo toward microtubule minus ends and to organize and position microtubule arrays such as the mitotic spindle. Cargo-specific adaptors engage with dynein to recruit and activate the motor, but the molecular mechanisms remain incompletely understood. Here, we use structural and dynamic nuclear magnetic resonance (NMR) analysis to demonstrate that the C-terminal region of human dynein light intermediate chain 1 (LIC1) is intrinsically disordered and contains two short conserved segments with helical propensity. NMR titration experiments reveal that the first helical segment (helix 1) constitutes the main interaction site for the adaptors Spindly (SPDL1), bicaudal D homolog 2 (BICD2), and Hook homolog 3 (HOOK3). In vitro binding assays show that helix 1, but not helix 2, is essential in both LIC1 and LIC2 for binding to SPDL1, BICD2, HOOK3, RAB-interacting lysosomal protein (RILP), RAB11 family-interacting protein 3 (RAB11FIP3), ninein (NIN), and trafficking kinesin-binding protein 1 (TRAK1). Helix 1 is sufficient to bind RILP, whereas other adaptors require additional segments preceding helix 1 for efficient binding. Point mutations in the C-terminal helix 1 of Caenorhabditis elegans LIC, introduced by genome editing, severely affect development, locomotion, and life span of the animal and disrupt the distribution and transport kinetics of membrane cargo in axons of mechanosensory neurons, identical to what is observed when the entire LIC C-terminal region is deleted. Deletion of the C-terminal helix 2 delays dynein-dependent spindle positioning in the one-cell embryo but overall does not significantly perturb dynein function. We conclude that helix 1 in the intrinsically disordered region of LIC provides a conserved link between dynein and structurally diverse cargo adaptor families that is critical for dynein function in vivo.